Perlindungan Hukum bagi Kreditur Akad Musyarakah dengan Menggunakan Akta Nominee - Siti Ayu Rahayu (Program Pascasarjana Universitas Ibrahimy, 2023)
The purpose of this journal research is to find out the guarantee provisions in musyarakah contracts in Islamic banking and legal protection for creditors in musyarakah contracts in Islamic banking that use nominee deeds. Normative juridical research methods use state approach, case approach, historical approach, competitive approach and contextual approaches (conceptual approach). The nature of this research is descriptive. The sources of legal materials used are primary legal materials and secondary legal materials. The nature of the research is descriptive analysis research and drawing conclusions using deductive methods. The results of this study indicate that the use of guarantee provisions in musyarakah contracts in Islamic banking has been carried out in accordance with positive law. Meanwhile, when connected with the Fatwa of the National Sharia Council, the use of collateral or collateral in a musyarakah contract is not appropriate. Meanwhile, preventive protection that can be carried out by banks is the principle of prudence and the principle of knowing your customer. In addition, the form of legal protection against claims from third parties caused by the guarantee of the nominee deed can be carried out by alternative dispute resolution with litigation and non-litigation efforts.